Prevalence of frailty and pain in hospitalised adult patients in an acute hospital: a protocol for a point prevalence observational study. Issue 3 (23rd March 2021) - Saunders, Rosemary; Crookes, Kate; Atee, Mustafa; Bulsara, Caroline; Bulsara, Max K; Etherton-Beer, Christopher; Ewens, Beverley; Gallagher, Olivia; Graham, Renee M; Gullick, Karen; Haydon, Sue; Nguyen, Kim-Huong; et al.
Abstract : Introduction: Frailty and pain are associated with adverse patient clinical outcomes and healthcare system costs. Frailty and pain can interact, such that symptoms of frailty can make pain assessment difficult and pain can exacerbate the progression of frailty. The prevalence of frailty and pain and their concurrence in hospital settings are not well understood, and patients with cognitive impairment are often excluded from pain prevalence studies due to difficulties assessing their pain. The aim of this study is to determine the prevalence of frailty and pain in adult inpatients, including those with cognitive impairment, in an acute care private metropolitan hospital in Western Australia. Methods and analysis: A prospective, observational, single-day point prevalence, cross-sectional study of frailty and pain intensity of all inpatients (excluding day surgery and critical care units) will be undertaken. Frailty will be assessed using the modified Reported Edmonton Frail Scale. Current pain intensity will be assessed using the PainChek smart-device application enabling pain assessment in people unable to report pain due to cognitive impairment. Participants will also provide a numerical rating of the intensity of current pain and the worst pain experienced in the previous 24 hours. Demographic and clinical information will be collected from patient files. The overall response rate of the survey will be reported, as well as the percentage prevalence of frailty and of pain in the sample (separately for PainChek scores and numerical ratings). Additional statistical modelling will be conducted comparing frailty scores with pain scores, adjusting for covariates including age, gender, ward type and reason for admission. Ethics and dissemination: Ethical approval has been granted by Ramsay Health Care Human Research Ethics Committee WA/SA (reference: 2038) and Edith Cowan University Human Research Ethics Committee (reference: 2020–02008-SAUNDERS). Findings will be widely disseminated through conference presentations, peer-reviewed publications and social media. Trial registration number: ACTRN12620000904976.